2023
DOI: 10.1111/trf.17501
|View full text |Cite
|
Sign up to set email alerts
|

Survey of blood collection and transfusion practices among institutions in Africa

Jeremy W. Jacobs,
Laura D. Stephens,
Danny A. Milner
et al.

Abstract: IntroductionDramatic improvements in blood transfusion have occurred during the last two decades. Transfusion medicine services and practices in Africa remain underexplored.MethodsA survey of blood bank/transfusion medicine (BBTM) practices, available blood products, blood product source(s), pre‐transfusion testing, and blood donor infectious disease testing methodologies across Africa was performed using the American Society for Clinical Pathology (ASCP) listserv. Survey recipients included hospital‐based lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The most recent Global status report on blood safety and availability issued by the WHO 11 shows that the prevalence of blood‐borne viruses in Low to Middle Income Countries (LMIC) and Low Income Countries (LIC) is approximately two orders of magnitude higher than it is in High Income Countries (HIC), causing the WHO to point out that ‘Prevalence of an infection among blood donations or the proportion of blood donations with a positive result are directly related to the safety of the blood supply, because they have an impact on the residual risk of distributed blood components for transfusion, and also on the risk due to errors in blood quarantine and release (even though test‐positive donations should be discarded)’. In a recent survey of blood collection and testing practices in Africa, 12 reported that a high percentage of respondents use suboptimal testing strategies, including Rapid Detection Tests (RDTs) 13 and antigen tests in lieu of Nucleic Acid Testing NAT 14 . While these testing strategies, imposed by economic factors, are undoubtedly improving the safety of transfused blood in LMIC and LIC, the increased risk of transfusion‐transmitted infections for chronically treated patients such as haemophiliacs, as modelled for HIV, 8 emphasises the need for the exposure of such patients to be minimised through pathogen reduction.…”
Section: Cryoprecipitate (‘Cryo’) Cryoprecipitate—pathogen Reduced (‘...mentioning
confidence: 99%
“…The most recent Global status report on blood safety and availability issued by the WHO 11 shows that the prevalence of blood‐borne viruses in Low to Middle Income Countries (LMIC) and Low Income Countries (LIC) is approximately two orders of magnitude higher than it is in High Income Countries (HIC), causing the WHO to point out that ‘Prevalence of an infection among blood donations or the proportion of blood donations with a positive result are directly related to the safety of the blood supply, because they have an impact on the residual risk of distributed blood components for transfusion, and also on the risk due to errors in blood quarantine and release (even though test‐positive donations should be discarded)’. In a recent survey of blood collection and testing practices in Africa, 12 reported that a high percentage of respondents use suboptimal testing strategies, including Rapid Detection Tests (RDTs) 13 and antigen tests in lieu of Nucleic Acid Testing NAT 14 . While these testing strategies, imposed by economic factors, are undoubtedly improving the safety of transfused blood in LMIC and LIC, the increased risk of transfusion‐transmitted infections for chronically treated patients such as haemophiliacs, as modelled for HIV, 8 emphasises the need for the exposure of such patients to be minimised through pathogen reduction.…”
Section: Cryoprecipitate (‘Cryo’) Cryoprecipitate—pathogen Reduced (‘...mentioning
confidence: 99%